IMPLEMENTATION OF SOCIAL SCIENCE LEARNING MATERIALS THROUGH TIKTOK SOCIAL MEDIA IN MOTIVATING 9TH GRADE OF HANG TUAH 4TH SURABAYA STUDENTS - Jonathan Acel Fabianrico; Ninik Indawati; Dwi Fauzia Putra (Media Inovasi Pendidikan dan Publikasi, 2023)
The results of initial observations on students while participating in social studies learning in grade 9 at SMP Hangtuah 4 Surabaya found that students' motivation in social studies learning needs to be improved. Students often look bored and bored while following social studies subjects. Learning method innovations using Tik Tok videos are expected to be able to motivate students in learning social studies lessons. This type of research is qualitative research with 12 informants from grade 9 students at SMP Hangtuah 4 Surabaya and one teaching teacher. Data collection techniques using interview guides. Data analysis technique using descriptive analysis. The findings of this study indicate that students have a stronger motivation to learn social studies lessongs by using Tik Tok videos. Tik Tok videos should be made creatively so as to add interest to students. The use of Tik Tok videos has limitations, especially in term of duration, so they should be designed as well as possible so that the material content in Tik Tok videos become more complete. The teaching teacher should also provide a web link that contains all the Tik Tok videos of social studies subject matter so that students can visit them without having to save them on student’s cellphones.